A High‐amylose Modifier Locus Revealed by Analysis of a Homozygous Amylose‐extender Mapping Population. Issue 3 (1st May 2015) - Wu, Yusheng; Huang, Ruijia; Auger, Donald; Campbell, Mark; Yen, Yang
ABSTRACT: Recent food industry applications have increased interest in high amylose starch. Starch from the maize endosperm is typically around 25% amylose, but increases to around 50% in plants that are homozygous for the recessive amylose‐extender1 ( ae1 ) allele. A maize ( Zea mays L.) line, GEMS‐0067 (Reg. no. GP‐550, PI 643420), has been demonstrated to produce starch with up to 70% amylose. We were interested in locating genetic modifiers that influence endosperm amylose in GEMS‐0067. An F1 population was made by crossing GEMS‐0067 with H99ae, the latter with an amylose content of approximately 55%. Generations were advanced to produce F2 and F3 populations. Amylose content of samples from the advanced generations was measured by amylose‐iodine colorimetry and the genotypes of F2 and F3 individuals were scored for polymorphisms of simple sequence repeat (SSR) markers. A major quantitative trait locus (QTL), which explained 43% of the total variance and demonstrated additive inheritance, was detected on the short arm of chromosome 5. The starch branching enzyme 1 ( sbe1) gene lies within the interval of this QTL. Sequences of sbe1 from both GEMS‐0067 and H99ae indicated that the two translated proteins had six amino acid polymorphisms. The amino acid sequence for GEMS‐0067 appeared to be unique, while H99ae was nearly identical to the translated sbe1 sequences represented in previous publications on this general topic. We proposed that sbe1 is a strong candidate gene for this QTL.